Some properties of Fundamental Complex functions - Abdul-Kadir, Fryad H. (Sulaimani Journal for Pure and Applied Sciences, 2009)
The purpose of this work is to define and study a new type of functions which have only essential singular points on a region in complex plane, so that several properties of this type of functions are given. Also we study the set of this type of functions algebraically to get some theorems and results.
Keywords: Fundamental complex functions; essential singular points; removable singular points; poles; analytic functions